PENGARUH PERSEPSI TERHADAP IKLAN DIGITAL PROGRAM ‘SMILING WEST JAVA’ TERHADAP CITRA DESTINASI WISATA DI JAWA BARAT DENGAN BRAND AWARENESS SEBAGAI VARIABEL MEDIASI - Auliyani, Fitri (JURNAL ILMIAH EDUNOMIKA, 2025)
This study analyzes the effect of public perception of the Smiling West Java digital advertising program on the image of West Java as a tourism destination, with brand awareness as a mediating variable. While digital marketing has become a primary strategy in tourism promotion and internet penetration in Indonesia is high (79.5% in 2024), the effectiveness of this regional digital advertising campaign has not been fully optimal. The West Java Tourism and Culture Office (2023) reported a significant increase in the production and distribution of promotional content through the official Smiling West Java channels. However, by the end of 2023, tourist visits had reached only 80% of the target of 218.7 million, with several destinations outside Lembang and Pangandaran experiencing stagnation or decline. Observations of the official Instagram account showed low user engagement and underutilization of promotional features. Using a quantitative causal research design with 166 respondents, multiple regression analysis and the Sobel test revealed that perception of digital advertising significantly influences brand awareness, and both variables significantly affect the tourism destination image. Brand awareness also significantly mediates this relationship. The findings provide practical insights for tourism managers to optimize emotionally engaging, informative, and interactive digital content to strengthen brand awareness and destination image. Keywords: digital advertising, brand awareness, tourism destination image, Smiling West Java, perception